The Clinical Application of MicroRNAs in Infectious Disease - Drury, Ruth E.; O’Connor, Daniel; Pollard, Andrew J. (Frontiers in Immunology, 2017)
MicroRNAs are short single-stranded non-coding RNA sequences that post-transcriptionally regulate up to 60% of protein encoding genes. Evidence is emerging that microRNAs are key mediators of the host response to infection, predominantly by regulating proteins involved in innate and adaptive immune pathways. MicroRNAs can govern the cellular tropism of some viruses, are implicated in the resistance of some individuals to infections like HIV, and are associated with impaired vaccine response in older people. Not surprisingly, pathogens have evolved ways to undermine the effects of microRNAs on immunity. Recognition of this has led to new experimental treatments, RG-101 and Miravirsen – hepatitis C treatments which target host microRNA. MicroRNAs are being investigated as novel infection biomarkers, and they are being used to design attenuated vaccines e.g. against Dengue virus. This comprehensive review synthesises current knowledge of microRNA in host response to infection with emphasis on potential clinical applications, along with an evaluation of the challenges still to be overcome.